Universal gate-set for trapped-ion qubits using a narrow linewidth diode laser - Nitzan Akerman; Nir Navon; Shlomi Kotler; Yinnon Glickman; Roee Ozeri (New Journal of Physics, 2015)
We report on the implementation of a high fidelity universal gate-set on optical qubits based on trapped ^88 Sr ^+ ions for the purpose of quantum information processing. All coherent operations were performed using a narrow linewidth diode laser. We employed a master-slave configuration for the laser, where an ultra low expansion glass Fabry–Perot cavity is used as a stable reference as well as a spectral filter. We characterized the laser spectrum using the ions with a modified Ramsey sequence which eliminated the affect of the magnetic field noise. We demonstrated high fidelity single qubit gates with individual addressing, based on inhomogeneous micromotion, on a two-ion chain as well as the Mølmer–Sørensen two-qubit entangling gate.